2001
DOI: 10.1021/jf010573a
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Active Components from Cedrus deodara

Abstract: An activity-directed fractionation and purification process was used to identify the antioxidant components of Cedrus deodara. Dried heartwood powder of C. deodara was first defatted with petroleum ether and then extracted with chloroform. The chloroform extract showed strong antioxidant activity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical. This fraction was then subjected to separation and purification using silica gel column chromatography. Three compounds with potent antioxidant activity were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 24 publications
(23 reference statements)
1
38
0
Order By: Relevance
“…R. communis has central nervous system (CNS) stimulant (Ferraz et al 1999), antitumor (Lin and Liu 1986), antifertility (Makonnen et al 1999), antifilarial (Titanji et al 1987), antiparasitic (Jacobson and Schlein 1999) and insecticidal (Alvarez Montes de Oca et al 1996) properties. C. deodara is known as an antioxidant (Tiwari et al 2001), anti-inflammatory, analgesic, immunomodulatory (Shinde et al 1999a,b) and a spasmolytic (Kar et al 1975). This study has revealed the macrofilaricidal properties of S. indicus and C. deodara that are known for other medicinal properties as mentioned above.…”
Section: Discussionmentioning
confidence: 57%
“…R. communis has central nervous system (CNS) stimulant (Ferraz et al 1999), antitumor (Lin and Liu 1986), antifertility (Makonnen et al 1999), antifilarial (Titanji et al 1987), antiparasitic (Jacobson and Schlein 1999) and insecticidal (Alvarez Montes de Oca et al 1996) properties. C. deodara is known as an antioxidant (Tiwari et al 2001), anti-inflammatory, analgesic, immunomodulatory (Shinde et al 1999a,b) and a spasmolytic (Kar et al 1975). This study has revealed the macrofilaricidal properties of S. indicus and C. deodara that are known for other medicinal properties as mentioned above.…”
Section: Discussionmentioning
confidence: 57%
“…Bark of this plant has been included in several traditional Ayurvedic polyherbal preparations for indications like inflammation, arthritic pain and dermal diseases [1]. Several botanical products from the C. deodara have shown diverse pharmacological activities: anti-spasmodic and anti-cancer against human epidermoid carcinoma of nasopharynx [2], spasmolytic [3], anti-fungal [4], anti-arthritic [5], anti-allergic [6,7], anti-inflammatory and analgesic [8,9], anti-oxidant [10], anti-filarial [11], and molluscicidal [12].…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the chemical constituents of C. deodara have led to the discovery of many compounds including lignans, terpenoids, and glycosides [4][5]. In continuation of the work in the area of natural products [6], C. deodara oil and extracts were examined for the presence of many sesquiterpenes [7] with potent insecticidal activities [8].…”
mentioning
confidence: 99%